Defending against Buffer-Overflow Vulnerabilities. - Padmanabhuni, Bindu; Tan, Hee Beng Kuan (Computer (00189162), 2011)
A survey of techniques ranging from static analysis to hardware modification describes how various defensive approaches protect against buffer overflow, a vulnerability that represents a severe security threat.